Development of white rust resistant Indian mustard (Brassica juncea L. Czern and Coss) strain, “DRMRIJ 12-40”: Development of white rust resistant Indian mustard (Brassica juncea L. Czern and Coss) strain, “DRMRIJ 12-40” - K H SINGH; A K THAKUR; GUMAN SINGH; BHAGIRATHRAM (Journal of Oilseeds Research, 2020)
White rust caused by Albugo candida (Pers. ex Lev.) Kuntze is one of the most devastating diseases of Crucifers and causes severe losses in Indian mustard (Brassica juncea). DRMRIJ 12-40 is an inbred line derived from a cross between Zem 2 (exotic germplasm) and JGM 1-11 followed by individual plant selection. Shuttle breeding was followed to advance and screen the segregating generations (F2 and F4) at IARI Regional Station, Wellington. This strain has expressed resistant reaction against white rust during multilocation testing under All India Coordinated Research Project on Rapeseed-Mustard.